The new sociology of economic behaviour - Fevre, Ralph, 1955- (New horizons in sociology., 2003)
What are the solid achievements of the sociology of economic behaviour? What have been the main failures and omissions? How will the subject develop? In this assured and timely volume, the author demonstrates how the sociology of economic behaviour was hijacked by the economic sociology which grew out of Parsons' interpretation of Weber.